Design and application of subaxial cervical pedicle screw placement guide device - Wang, Qiang (Exp Ther Med, 2019)
In the present study, a novel subaxial cervical pedicle screw placement guide device was designed and developed. In cervical specimens (C3-C7), a pedicle screw was inserted into the left pedicle using the guide device with a keyhole partial laminectomy and tapping technique, and the right pedicle by drilling using the Abumi technique. After removing the pedicle screws, the channel wall of each pedicle screw was probed with a pedicle probe. The vertebral body was then dissociated for direct observation of the screw channel. Among the 10 specimens, 2 of the 50 pedicles (4%) in the guide device group were perforated. Screw placement failed in 8 of 50 pedicles (16%) in the Abumi technique group. Significant differences were observed in the outcomes for the guide device and Abumi technique groups. The subaxial cervical pedicle screw placement guide device developed in the present study decreased the failure rate of pedicle screw placement.